(untitled) (Journal of the College of Basic Education, 2022)
This research deals with the beginning of the emergence of the democratic movement in the Arab Gulf in general, and Kuwait in particular, and the causes and conditions experienced by the Arab Gulf region, which witnessed the spread of democratic ideas and principles. Kuwait, as one of these countries that witnessed the emergence of a national movement, whose objectives were concentrated in achieving political, social and cultural reform represented in limiting the powers of the ruler and his monopoly over the reins of political and economic matters as a result of internal and external circumstances and factors, by forming an elected legislative council and achieving a level of social justice.